Factors influencing farmers' satisfaction with the quality of agricultural extension services. (April 2021) - Kassem, Hazem S.; Alotaibi, Bader Alhafi; Muddassir, Muhammad; Herab, Ahmed
Highlights: Farmers had lowly participated in the extension services provided. Receiving information on the diagnosis of pests and diseases has a priority by farmers. The diversity of services was the lowest-ranked quality attribute observed by farmers. Farmers' participation in extension services significantly influences their satisfaction. Abstract: Assessing farmers' satisfaction with the quality of agricultural-extension services is essential for developing extension programs that comply with farmers' needs and agroecological conditions. This study aimed to determine factors influencing farmers' satisfaction with extension services. Data were collected through a questionnaire from a random sample of 393 farmers in the Kafr El Sheikh governorate. Farmers assessed the quality of extension services by five main indicators: (1) availability, (2) accessibility, (3) diversity, (4) relevance, and (5) effectiveness. Descriptive statistics and a logistic-regression model were used to analyze the data. Results showed that farmers had lowly participated in the provided extension services. The accessibility of services was ranked first with regard to satisfaction, while diversity of services was the lowest-ranked quality attribute. Results also revealed that factors significantly influencing farmers' satisfaction included farm size, diversity of farming activities, annual income, and participation in extension services. Results provide practical implications for policy makers to support smallholder farmers by providing high-quality extension programs.